The Effect of Educational Intervention Based on Protection Motivation Theory on Mothers' Behaviors about Prevention of Home Accidents in Children under 5 Year Old - Farbod Ebadi Fardazar; Syyedeh Shahrbanou Hashemi; Mahnaz Solhi Solhi; kamyar mansori (Mazandaran University of Medical Sciences, 2016)
Introduction and Purpose: Accidents are the first cause of death in children under 5 years, especially in low- and middle-income countries. The aim of this study is to determination the effect of Educational intervention on promotion of prevention behaviors of home accidents in mothers with children less than 5 year in Joibar city based on protection motivation theory (PMT) in 2015. Methods: In this controlled interventional study 190 mothers with children less than 5 year were participated (95 in case group and 95 incontrol group).The data collection toolwas researcher made questionnaire based on the structures of protection motivation theory.After done pre-test and the results obtained from it, appropriate educational intervention designed and was conducted only in case group. Then two months after the educational intervention,evaluation was done and data into SPSS 20software and by using statistical testsT-test، Paired T test ، chi _square، Pearson correlation coefficient and regression analysis was analyzed. Results: Statistically significant difference was found between mean scores of all structures of PMTin the case and control groups after the educational intervention, so that in all cases in the case group was better than control group (p<0.05). There was a significant difference between the mean scores of all structures of PMT in case group in before and after the educational intervention (p<0.05), Whereas no significant difference was seen between mean scores of all structures in control group in before and after the educational intervention (p>0.05). Conclusion: The results of this study showed that PMT can be used as a framework in designing educational programs in order to promotion of prevention behaviors of home accidents in mothers with children less than 5 year.